The performance of European SRI funds investing in bonds and their comparison to conventional funds - Leite, Paulo (2018)
This paper evaluates the performance of European SRI fixed-income funds domiciled in France and in Germany compared to characteristics-matched conventional funds. Fund performance is evaluated by means of conditional multi-factor models that allow for both time-varying risk and performance. The results show that SRI balanced funds perform similarly to conventional funds, whereas SRI bond funds significantly outperform their peers. The outperformance of SRI bond funds seems more related to their government (and not their corporate) bond holdings. Compared to conventional funds, SRI funds are significantly less exposed to bonds issued by the countries most affected by the Euro sovereign debt crisis, which is consistent with more conservative and long term-oriented investment strategies.